Psychometric Properties of the Adapted Jordanian Version of the Behavioral Assessment System for Children (BASC) - Abojedi, Amjed; Al-Sheikh, Ahmad (Jordan Journal of Educational Sciences, 2010)
This study aims at examining the psychometric properties of the adapted Jordanian version of the Behavioral Assessment System for Children (BASC). A sample of 739 students (4th, 5th, 6th and 7th grades), with ages between 9 to 11 years was selected from 17 schools in Amman. Statistical analysis of the data showed that the inventory items correlated medium to high with its relevant dimensions, and the goodness of fitness indices conformed to the original version. Furthermore, internal consistency reliability ranged from 0.65-0.89, and test-retest reliability indices ranged from 0.70-0.87. The inventory also had discriminated between students who were referred to counselors and those who were not. Standardized T scores were derived for the inventory subscales to give better interpretation and allow for plotting student’s profile.